A tale of two effusions diagnosing and managing pleural and pericardial empyema (Indian Journal of Case Reports, 2024)
A male in his early 50s with no comorbidities presented with a weeklong history of left-sided chest pain, breathlessness, and cough with yellow–green expectoration. Over 4 months, he reported a 5 kg weight loss and decreased appetite. Investigations revealed mild anemia, electrolyte imbalances, elevated erythrocyte sedimentation rate, and alkaline phosphatase. An electrocardiogram showed low-voltage complexes, and an echocardiogram detected pericardial effusion. A chest X-ray showed bilateral pleural effusion. Ultrasound-guided thoracentesis indicated pleural and pericardial empyema. Sputum tests identified Proteus mirabilis and pericardial fluid grew Escherichia coli. After the therapeutic intervention, the patient initially improved but later worsened, requiring mechanical ventilation, and inotrope support. On the 5th day of admission, he suffered a cardiac arrest and expired despite resuscitative efforts.